Pengembangan Aplikasi Pemasaran Ikan Untuk UMKM dan Nelayan Batam dengan Pendekatan User Centered Design (UCD) dan Usability Testing - Ari Novriansyah; Dwi Ely Kurniawan (Indonesian Society of Applied Science, 2022)
This study aims to design a fish trading application for SMEs and fishers in Batam. Batam is an area surrounded by the sea; most of the population makes a living as fishermen. The restrictions on community activities due to the Covid-19 pandemic have resulted in several weakening businesses where fishers and MSMEs have difficulty selling and distributing to consumers. The study took a case study on Tibelat Farm, an MSME, and anglers who cultivate fish and sell various consumption fish and ornamental fish. The application design uses the Laravel Framework with a UCD approach (User Centered Design), which involves the user in the business model to reach a broader market and complete available information. The results of the local community survey still have no confidence in online transactions, so in the design, they choose the pay-on-site or COD (Cash on Delivery) model. As an evaluation of the usability level using the SUS scale (System Usability Scale). The study results showed a SUS score of 57.58 which means that the application is functionally perfect and can be accepted by users.